A REPRESENTAÇÃO DA MULHER NEGRA EM MENINO DE ENGENHO, DOIDINHO E BANGUÊ DE JOSÉ LINS DO REGO: uma análise sob a perspectiva das confluências histórico-sociais - NASCIMENTO, Evany da Conceição do (2023)
The aim of this dissertation was to analyze the representations of black women in the novels of the Sugarcane Cycle - Menino de Engenho, Doidinho and Banguê - by José Lins do Rêgo from the perspective of historical-social transitions. It was considered that the production process of the mills, described in the novels of the prose writer from Paraiba, carries the model of the slave society, in which the mill owner, who is white and owns the property, can use the bodies of black people as objects, be it for work or to satisfy other needs. In this way, the research developed to the objective was explanatory and based on the dialectical Marxist method, based on the bibliographic material prepared by theorists dealing with topics related to the corpus under study, including literary excerpts of the object and also of theory and literary criticism, Rallo (2005), Eagleton (2019), Candido (1998; 2014;), Compagnon (2010), Zolin (2019), Chartier (2002), Perrot (2022), Lerner (2019; 2022), Bosi (2015; 2002), Castello (1961), Coutinho (1980), Gonzalez (2020), Davis (2016), Saffioti (2013; 2015), among others. Because it is a sequential, trilogical first-person narrative, it was possible to identify in the personal speeches a context of superpower that ruled over black women in the post-abolition context of the Brazilian Northeast during the Sugar Period. The analysis contained in this work reflected a synthesis of the objectified subjects from the perspective of machismo, racism and classism, and the main actors of these devices that established in society the stigmatized image of the black woman: the sensual, sexist Also “Active ", "Mammys" and "The Servant" have considered how these models of stereotypical applicability play out in today's society in terms of the silencing and erasure of black women.